Strategi Pendayagunaan Zakat Produktif: Studi BAZ Kabupaten Sukabumi Jawa Barat - Aab Abdullah (Institut Agama Islam Sahid Bogor, 2020)
Zakat is one of the main components in the Islamic economic system, it becomes a driving engine for the balance between the rich and the poor. His position is increasingly needed when faced with socio-economic problems that are not in favor of the poor. As social control, zakat does not make excessive differences between rich people and poor people, it makes wealth not only revolves around rich people, as mentioned in the QS. Al-Hasyr verse 7. So beneficial zakat is that the Caliph Abu Bakr fought those who did not want to pay zakat.The problems of zakat that are faced today are very complex, starting from the presence of some people who do not want to pay zakat, the distribution of zakat that has not been neatly arranged to the problem of fiqh regarding the development and ijtihad for productive zakat models. This last issue is the subject of this paper.Productive zakat is to make zakat money not only consumptive in the sense that it is immediately consumed, but zakat assets are used for business capital in order to alleviate poverty for zakat mustahik. With this venture capital, it is hoped that the zakat mustahik will one day become a muzaki.The zakat management strategy carried out by BAZ Sukabumi City is in the form of